Reinventing the economic history of industrialisation - Bruland, Kristine; Gerritsen, Anne; Hudson, Pat, 1948-; Riello, Giorgio (McGill-Queen's University Press, 2020)
"The Industrial Revolution is central to the teaching of economic history. It has also been key to historical research on the commercial expansion of Western Europe, the rise of factories, coal and iron production, the proletarianization of labour, and the birth and worldwide spread of industrial capitalism. However, perspectives on the Industrial Revolution have changed significantly in recent years. The book's interdisciplinary approach - with contributions on the history of consumption, material culture, and cultural histories of science and technology - offers a more global perspective, arguing for an interpretation of the industrial revolution based on global interactions that made technological innovation and the spread of knowledge possible. Through this new lens, it becomes clear that industrializing processes started earlier and lasted longer than previously understood. Reflecting on the major topics of concern for economic historians over the past generation, Re-inventing the Economic History of Industrialisation brings this area of study up to date and points the way forward."--